Neuropathogenesis of a mouse-adapted porcine epidemic diarrhea virus infection in suckling mice - Kotani, Osamu; Shirato, Kazuya; Nagata, Noriyo; Ikeda, Hidetoshi; Takahashi, Kimimasa; Taguchi, Fumihiro (Journal of general virology, 2013)
A mouse-adapted porcine epidemic diarrhea virus, MK-p10, showed higher neurovirulence in suckling mice than a non-adapted MK strain. There was no difference in virus growth, whereas clear differences between these two virus infections existed in the type of target cells infected, the spread of virus and the cytokine levels produced in the brain. In the early phase of infection, neurons, astrocytes and neural progenitor cells were infected by MK-p10, whereas neural progenitor cells were the only target cells infected by MK. On days 4–5 post-inoculation, MK-p10 antigens were distributed in a number of neurons in a wide area of the brain; however, antigens were restricted in MK infection. In moribund mice in both infection groups, viral antigens were found in a wide area of the brain. The wide spectrum of initial target cells following MK-p10 infection, as well as its faster spread in the brain, may be evidence of enhanced virulence in suckling mice.